2005
DOI: 10.1086/432256
|View full text |Cite
|
Sign up to set email alerts
|

AGN Host Galaxies at z  ~ 0.4-1.3: Bulge-dominated and Lacking Merger-AGN Connection

Abstract: We investigate morphological structure parameters and local environments of distant moderate-luminosity active galactic nucleus (AGN) host galaxies in the overlap between the HST/ACS observations of the Great Observatories Origins Deep Survey (GOODS) and the two Chandra Deep Fields. We compute near-neighbor counts and BViz asymmetry (A) and concentration (C) indices for ≈35,500 GOODS/ACS galaxies complete to , including z ≈ 26.6 850 the resolved hosts of 322 X-ray-selected AGNs. Distributions of (1) This impl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
222
5
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(255 citation statements)
references
References 28 publications
27
222
5
1
Order By: Relevance
“…The lack of signatures for frequent strong interactions is consistent with the findings at similar redshifts by Grogin et al (2005), Pierce et al (2007), Gabor et al (2009), andCisternas et al (2011). One major difference between the first two of these and our analysis is that they did not account for the potential influence of an optical nucleus.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of signatures for frequent strong interactions is consistent with the findings at similar redshifts by Grogin et al (2005), Pierce et al (2007), Gabor et al (2009), andCisternas et al (2011). One major difference between the first two of these and our analysis is that they did not account for the potential influence of an optical nucleus.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Li et al (2008), found no evidence for an excess of close companion galaxies near Type 2 AGN in the SDSS. These results agree with a number of investigations of the host galaxies of AGN at z ∼ 1 (Grogin et al 2005;Pierce et al 2007;Gabor et al 2009). …”
Section: T M Heckmansupporting
confidence: 92%
“…One advantage of our study is a combination of visual and analytic measures of galaxy structure over a wide range in redshift, which enables us to compare our results to a broader subset of relevant work from the literature. We are generally consistent with earlier studies which used analytic measures of AGN host structure, typically at z < 1 (Grogin et al 2005;Pierce et al 2007). Some of the differences between the AGNs and inactive galaxies in these earlier studies, such as higher early-type fractions or bluer colors among AGNs, are due to the improper choice of control samples, for example through matching by a blue optical luminosity rather than stellar mass.…”
Section: Comparison With Existing Studies Of X-ray Selected Agnssupporting
confidence: 91%
“…In general, these studies have either used analytic measures of structure, such as light profile fitting, pixel distribution statistics or moment measures (Grogin et al 2003(Grogin et al , 2005Pierce et al 2007;Gabor et al 2009;Simmons et al 2011;Schawinski et al 2011;Böhm et al 2013;Villforth et al 2014) or visual classification using a number of special-purpose schemes (Schawinski et al 2007(Schawinski et al , 2010Cisternas et al 2011;Kocevski et al 2012;Cimatti et al 2013). Some studies of more luminous optically-unobscured AGNs have also been undertaken, involving the careful subtraction of nuclear point sources to reveal the host galaxy more clearly (e.g., Bahcall et al 1997;McLeod & McLeod 2001;Dunlop et al 2003;Jahnke et al 2004;Sánchez et al 2004;Guyon et al 2006;Veilleux et al 2009).…”
Section: Introductionmentioning
confidence: 99%